2008
DOI: 10.1007/s11606-008-0777-8
|View full text |Cite
|
Sign up to set email alerts
|

Risks and Advantages of Detecting Individuals Unfit to Drive: A Markov Decision Analysis

Abstract: Because of the expected difficult application and cost of road tests and annual screening by clinicians, the most acceptable strategy from public health, clinical, and individual points of view is likely to be no screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 36 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…Although increased age is associated with a higher proportion of cognitively impaired drivers, mandatory age-based driver testing has not been shown to decrease crash rates 61. Decision analysis studies have not consistently revealed the benefits of systematically screening and evaluating demented drivers 62. Cleary, more studies are needed in this area of the benefits and risks of screening for cognitively impaired older adults.…”
Section: Psychometric Testsmentioning
confidence: 99%
“…Although increased age is associated with a higher proportion of cognitively impaired drivers, mandatory age-based driver testing has not been shown to decrease crash rates 61. Decision analysis studies have not consistently revealed the benefits of systematically screening and evaluating demented drivers 62. Cleary, more studies are needed in this area of the benefits and risks of screening for cognitively impaired older adults.…”
Section: Psychometric Testsmentioning
confidence: 99%
“…Studies are needed to compare the benefits and costs of mandatory reporting to driver licensing authorities with voluntary reporting, although studies in other illnesses are not supportive of mandatory reporting (McLachlan et al, 2007). Decision analysis studies have not shown the benefits of systematically screening and evaluating drivers with dementia (Retchin and Hillner, 1994;Leproust et al, 2008). Some studies have noted positive impact on driving of cognitive stimulation (Edwards et al, 2005) and exercise interventions on older adults (Marmeleira et al, 2009), although these studies were not performed in patients with dementia.…”
Section: The Physician's Legal and Ethical Obligationsmentioning
confidence: 99%
“…Recent studies as well as current models of older driver behavior all underline the fact that driving competency is multi-factorial and that the multiple factors involved interact with one another (Anstey et al, 2005;Dickerson and Bédard, 2014;Kamenhoff, 2008;Michon, 1985;Wood et al, 2008). However, the precise cognitive and motor components as well as their interactions have yet to be fully revealed (Bédard et al, 2008;Fildes 2008;Leproust et al, 2008;Wheatley and Di Stefano, 2008). Although very informative, models have failed to generate indicators of driving safety.…”
Section: Introductionmentioning
confidence: 99%